Leena Hibbert: capstone - Hibbert, Leena, artist (Colorado State University. Libraries, 2014)
The artist's statement: As an artist I delight in the exploration of form in all its incarnations. I appreciate the versatility of metal as it takes its shape, and the possibilities are only limited by my skills and imagination. Much of my work to date has been sculptural jewelry that functions as wearable art. However, most recently my work has turned toward experimentation with form. I am drawn to nature which inspires this organic work. Through this exploration, I find the satisfaction of melding soft form with the perceived rigidity of metal. I feel a deep connection with the metalsmiths of the past. It is amazing to me that the techniques employed by the earliest artisans have lasted through the millennia with minimal change. This knowledge ties me to history in a way that I really appreciate. My fascination allows me to draw inspiration from historical artifacts from both recent and ancient history. This appreciation for history also inspires me to explore my own heritage. My newest work is informed by my Irish - Celtic lineage because I know so little about that side of my family. My work is my way of connecting with the ancestors that I cannot possibly know through the largely unchanged processes of metalsmithing.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.